Metal-Induced Crystallization in Metal Oxides - Lermusiaux, Laurent; Mazel, Antoine; Carretero-Genevrier, Adrian; Sanchez, Clément; Drisko, Glenna L (Accounts of chemical research, 2022)
ConspectusThe properties of a material depend upon its physical characteristics, one of these being its crystalline state. Next generation solid-state technologies will integrate crystalline oxides into thermal sensitive processes and composite materials. Crystallization of amorphous phases of metal oxides in the solid state typically requires substantial energy input to induce the amorphous to crystalline phase transformation. In the case of silica, the transformation to α-quartz in a furnace occurs above 1300 °C and that of titania, above 400 °C. These calcination processes are costly in energy but also often degrade complex material architectures or compositions.Thus, low temperature crystallization techniques are required that preserve macro- and mesostructures and complex elemental composition (e.g., organic-, metal-, and semiconductor-metal oxide hybrids/composites). Some solution-based techniques exist to directly fabricate crystalline metal oxides. However, these are not always compatible with the specificities of the system or industrial constraints. A postsynthetic, solid-state approach that reduces crystallization temperature in metal oxides is metal-induced crystallization (MIC).MIC is the introduction of catalytic amounts of a cation, which can be an s-block, p-block, or d-block cation, that migrates through the solid metal oxide lattice. The cation is thought to temporarily break metal oxide bonds, allowing [MO ] polyhedra to rotate and reform bonds with neighboring [MO ] groups in a lower energy crystalline phase. Depending on the system, the cation can favor or defavor the formation of a particular crystalline phase, providing a means to tune the purity and crystalline phase ratios. An advantage of MIC is that, although the crystallization occurs in the solid state, the crystallization process can be accomplished for particle suspensions in liquid media. In this case, the energy required to induce the crystallization can come from, for example, a microwave or an ultrasound bath. The crystallization of particles in suspension avoids aggregation from particle-particle sintering. In the case of thin films, the energy for crystallization typically comes from a laser or calcination.MIC is only recently being used as a low temperature metal oxide crystallization technique, despite being widely used in the semiconductor industry. Here, the mechanism and previous studies in MIC are presented for titania, silica, and other oxides. The beauty of this technique is that it is extremely easy to employ: cations can be incorporated into the system postsynthetically and then are often expelled from the lattice upon phase conversion. We expect MIC to enrich materials for photochromic, optoelectronic, catalyst, biological, and other applications.